A half-bridge HTS transformer–rectifier flux pump with two AC field-controlled switches. (19th June 2018) - Gawith, J D D; Geng, J; Li, C; Shen, B; Zhang, X; Ma, J; Coombs, T A
Abstract: Flux pumping provides a method of inductively magnetizing superconducting coils and can provide thermal, electrical and mechanical isolation between cryogenic environment and power supply. This offers the possibility of lower cryogenic loading and more flexible arrangements for superconducting magnet systems. This paper reports on the performance and analysis of a high-temperature superconducting (HTS) half-bridge transformer–rectifier type flux pump using two switching elements formed by applying AC magnetic field to sections of HTS. Theory of operation is presented followed by results from an experimental prototype which are compared with SPICE simulation. There is good qualitative agreement between simulation and experiment and all current, voltage and power waveforms from experiment are presented. This work represents a step forward in the understanding of the operation of HTS transformer–rectifier flux pumps and shows that SPICE simulation can provide designers of future HTS flux pumping systems with a useful tool for making design decisions.